pH AND WATER QUALITY DETERMINATION AF STABILIZED SOIL IN ACID ENVIRONMENT - MUHAMMAD THURSINA CAHYA (Universitas Muhammadiyah Yogyakarta, 2003)
pH AND WATER QUALITY DETERMINATION AF STABILIZED SOIL IN ACID ENVIRONMENT